2023
DOI: 10.3389/fpls.2023.1218445
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of phosphate-solubilizing bacterium Pantoea rhizosphaerae sp. nov. from Acer truncatum rhizosphere soil and its effect on Acer truncatum growth

Abstract: The Acer truncatum Bunge, widely distributed in North China, shows excellent tolerance to low-P soils. However, little information is available on potential phosphate-solubilizing bacterial (PSB) strains from the A. truncatum rhizosphere. The objectives of this work were to isolate and characterize PSB from A. truncatum rhizosphere soil and to evaluate the effect of inoculation with the selected strain on A. truncatum seedlings. The strains were characterized on the basis of phenotypic characteristics, carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Thus, NBRIP medium used in this investigation was adopted to demonstrate solubilization by the isolates as halos are easy to detect by color change around the colony. In addition, it was demonstrated that solubilization obtained with TCP as sole P source in the medium was significantly greater than in the presence of rock phosphate (Azaroual et al, 2020;Ma et al, 2023). Thus, we used TCP as P source in our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, NBRIP medium used in this investigation was adopted to demonstrate solubilization by the isolates as halos are easy to detect by color change around the colony. In addition, it was demonstrated that solubilization obtained with TCP as sole P source in the medium was significantly greater than in the presence of rock phosphate (Azaroual et al, 2020;Ma et al, 2023). Thus, we used TCP as P source in our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…It has certain ornamental and medicinal value [16][17][18]. Acer Truncatum can still grow normally in soil with low phosphorus content and has certain stress resistance [19], which may be related to the abundance of endophytic fungi in its body. Endophytic fungi are widely distributed in plants and form a mutualistic relationship with their hosts.…”
Section: Introductionmentioning
confidence: 99%